Predictors of recycling behaviour intentions among urban Lithuanian inhabitants - Pikturnienė, Indrė; Bäumle, Greta (Journal of Business Economics and Management, 2016)
In countries where no incentives for recycling prevail, individual recycling is grounded on citizens’ consciousness and everyday efforts. Governmental actions can be effective only after understanding factors for recycling behaviour, and fostering them. Since the primary target group of recycling in Lithuania are urban inhabitants, it is important to determine what sub-segments of this group are the most likely to become innovators and early adopters in the field, and to identify what are the most important predictors of their recycling intentions. The aim of the study was to determine how values affect attitude elements towards recycling and what attitude elements and (or) recent recycling behaviour are the most important predictors of intentions to recycle; and to investigate what demographic groups among Lithuanian urban inhabitants are the most likely to be engaged in recycling. Survey using an instrument that allowed determining values, attitudes, subjective norm, perceived behavioural control, actual level of recycling, and link them to the intentions to recycle was performed among urban Lithuanian inhabitants. Results suggest two main strategies for social change managers: informing consumers to increase favourable attitudes towards recycling, and inducing recycling habit. The efforts should be primarily targeted towards educated people over 35, irrespective of gender.